José Mármol's Amalia (1851, 1855): The Politics of Consumption and the Limits of Liberalism. Issue 1 (2nd January 2019) - Hallstead, Susan R.
Abstract : Praised for its value as a political and/or historical romantic novel, Amalia is also one of the first and most detailed novels of the period to offer modern readers a snapshot of how consumption in literature – in a very broad sense, from clothing to decorative items – played a central role not only in mapping the transition from a pre-capitalist to a capitalist order, but also in exposing the key ideological and aesthetic tensions of the time (such as the rift between Unitarian and Federalist camps as well as gender and class tensions that continued in post-colonial Argentina). Keeping this in mind, this study considers how José Mármol's treatment of luxury items in Amalia changed from the 1851 version (written before the fall of the Rosas dictatorship) to the 1855 one (written afterwards, in a much more conciliatory tone). While only 4 years had passed between these two editions, the changes in the descriptions of consumptive patterns point to the fact that consumption was not merely a colourful background in which to situate the novel's political goals. Rather, consumption was political and, for Mármol, it was part and parcel of constructing a modern, liberal, romantic subject.